Persepsi Masyarakat terhadap Kandungan Alkohol Pada Kosmetik - Nurkhasanah Nurkhasanah; Amalya Nurul; Farah Qistih Albab (Faculty of Pharmacy, Universitas Gadjah Mada)
Perception is an individual response about something that can be influenced by knowledge. Good individual knowledge of alcohol will affect their perception of alcohol-containing product. The MUI fatwa permits the use of alcohol in cosmetics. The purpose of this study was to observe the perception of alcohol content in cosmetics. The observation was carried out using a questionnaire technique with a nonprobability sampling technique with accidental sampling. The questionnaire was conducted by Pearson correlation test, validity test, reliability test, normality test, chi-square test, and description. In this study, using 98 respondents and get an average value of knowledge about cosmetics 6,73 with SD value of 0,49; knowledge of alcohol 4,54 with SD 1,17 and behavior with SD 1,46. There is a relationship between age with the level of cosmetic knowledge with p-value <0.05. As many as 46.94% stated, the halal label's urgency on cosmetics is very important and 39.80% is important, where the religion of the individual influences the urgency level of cosmetics halal. The urgency of halal labels on cosmetics is high in line with the behavior when buying cosmetics. The 81.63% of respondents stated that halal labels on cosmetic products affect the interest in buying cosmetics. As many as 61.24% of respondents have the perception that halal cosmetics do not contain alcohol. The Pearson halal label correlation test confirms this obtained a p-value value of 0.024 that the halal label influences respondents' perceptions. Individuals were having a perception that cosmetics with halal labels do not contain alcohol, which is influenced by halal labels' knowledge.